Factors forming employee motivation influenced by regional and age-related differences - Hitka, Miloš; Rózsa, Zoltán; Potkány, Marek; Ližbetinová, Lenka (Journal of Business Economics and Management, 2019)
The aim of the paper is to define and quantify the differences in employee motivation depending upon the selected regions and the age of employees. The research was carried out in 2017. Sampling unit consisted of 7,594 respondents – employees from the selected eastern European countries, members of the European Union, mainly the Slovak and Czech Republic, as well as selected regions outside the European Union, Russia and China. Data gathered from the questionnaires were evaluated using descriptive statistics and tested by Tukey's HSD at the level of significance of 5%. The ANOVA Variance Analysis was used to compare each sampling unit in relation to the age and the country. Most of the differences in motivation factors were found in the countries of China and Russia. It can be due to different cultural values, especially because of the power gap and the preferred principle of seniority and collectivism in China. Differences in the level of motivation, i.e. motivation factors especially in relation to the age were observed in the analysed regions. Incentive plans for intercultural teams in order to enable employers to choose motivation factors effectively were designed following the conclusions presented in the paper. Fundamental patterns of cultural differences as well as age-related differences predicting motivational preferences can be taken into consideration when selecting the motivation factors.